KnowledgeBoat Logo

Mathematics

Taking A = 30°, verify that

(i) cos4 A - sin4 A = cos 2A

(ii) 4 cos A cos (60° - A) cos (60° + A) = cos 3A.

Trigonometrical Ratios

14 Likes

Answer

(i) To verify,

cos4 A - sin4 A = cos 2A

Substituting value of A in L.H.S. of the above equation, we get :

cos4 Asin4 Acos4 30°sin4 30°(32)4(12)491611681612.\Rightarrow \text{cos}^4 \space A - \text{sin}^4 \space A \\[1em] \Rightarrow \text{cos}^4 \space 30° - \text{sin}^4 \space 30° \\[1em] \Rightarrow \Big(\dfrac{\sqrt{3}}{2}\Big)^4 - \Big(\dfrac{1}{2}\Big)^4 \\[1em] \Rightarrow \dfrac{9}{16} - \dfrac{1}{16} \\[1em] \Rightarrow \dfrac{8}{16} \\[1em] \Rightarrow \dfrac{1}{2}.

Substituting value of A in R.H.S. of the above equation, we get :

⇒ cos 2A = cos 2(30°) = cos 60° = 12\dfrac{1}{2}.

Since, L.H.S. = R.H.S.

Hence, proved that cos4 A - sin4 A = cos 2A.

(ii) To verify,

4 cos A cos (60° - A) cos (60° + A) = cos 3A.

Substituting value of A in L.H.S. of the above equation, we get :

4 cos 30° cos (60° - 30°) cos (60° + 30°)4 cos 30° cos 30° cos 90°4×32×32×00.\Rightarrow \text{4 cos 30° cos (60° - 30°) cos (60° + 30°)} \\[1em] \Rightarrow \text{4 cos 30° cos 30° cos 90°} \\[1em] \Rightarrow 4 \times \dfrac{\sqrt{3}}{2} \times \dfrac{\sqrt{3}}{2} \times 0 \\[1em] \Rightarrow 0.

Substituting value of A in R.H.S. of the above equation, we get :

cos 3(30°)=cos 90°=0.\Rightarrow \text{cos 3(30°)} = \text{cos 90°} = 0.

Since, L.H.S. = R.H.S.

Hence, proved that 4 cos A cos (60° - A) cos (60° + A) = cos 3A

Answered By

4 Likes


Related Questions